Mechanistic comparison of N2 and H2 dilution effects on soot formation processes in laminar ethylene diffusion flames. Issue 1 (31st December 2022) - Khabazipur, Arash; Eaves, Nick A.
Abstract: Fuel dilution is commonly used to reduce soot emissions from combustion engines or control carbon black morphology during fuel pyrolysis. Dilution has both physical and chemical effects on soot formation; however, the impact of fuel dilution on each soot formation process has not been fully understood yet. This study investigates the differing effects of dilution with H2 and N2 on particle inception and surface growth by hydrogen abstraction carbon addition (HACA) and polycyclic aromatic hydrocarbon (PAH) adsorption in ethylene/air laminar coflow diffusion flames. Applicable correlations are introduced to predict the conversion of carbon to soot to an accuracy of 96.5% at different dilution ratios. Both diluents result in significant reductions in HACA and PAH adsorption, up to 42% and 68%, respectively, at 40% dilution, with greater reductions for dilution with N2 . For replacement cases, more reduction comes from a considerable change in the flame length, resulting in reduced high-temperature particle residence time. Combined, these effects significantly reduce HACA and PAH adsorption by up to 85% and 60%, respectively, for mixed replacement. Reduced acetylene and PAH concentrations for both gases, respectively, reduce HACA and PAH adsorption rates. Earlier in the flame, reduced PAH formation in the inception zone of the flame results in lower inception rates, producing fewer primary particles for subsequent growth processes. Comparing the two diluents, N2 reduces acetylene and PAH concentrations by 12% and 18%, respectively, more than H2, and delays PAH formation in the flame, which delays inception and surface growth.